Involvement of the endonuclease domain of the EcoR124I restriction-modification complex in interdomain communication - Shamayeva, Katsiaryna (Jihočeská univerzita, 2015)
Type I restriction-modification (R-M) enzymes recognize specific sequences on foreign DNA invading the bacterial cell. At a first sight, also host DNA containing the specific target site for Type I R-M enzyme would cleavage, too, but this doesn't happen as the enzymes are able to distinguish between hostband foreign DNA. Normally the specific sequence on host DNA is either fully methylated or the Type I R-M enzyme recognizes the hemi-methylated state of the DNA, switches to the modification mode and methylates the second strand of the hemi-methylated DNA. Recognition of unmethylated foreign DNA invading the bacterial cell from the outer environment leads to a switching to the restriction mode, initiating endonuclease activity. The R-M complex tightly bound to the recognition sequence on foreign DNA then starts to translocate dsDNA in an ATP-dependent manner towards the stationary enzyme over up to several thousand base pairs. When DNA translocation is finally stalled, the enzyme complex introduces a double strand break, seemingly in a random site distant from the recognition sequence. Multi-subunit structure determines complex behavior of Type I R-M enzymes. The fully assembled Type I R-M enzyme consists of five subunits which are encoded by hsd genes (host specificity for DNA): one copy of HsdS subunit together with two copies of HsdM subunit form the trimeric HsdS1-HsdM2 methyltransferase complex which recognizes and binds to a specific DNA sequence and bears the methylation function. The fully assembled HsdS1-HsdM2-HsdR2 complex possesses ATP-dependent DNA translocation and endonuclease activities located on its HsdR subunits. The X-ray crystal structure of HsdR of EcoR124I with bound ATP gives a first insight of structural/functional correlation in the HsdR subunit. In this work the involvement of the endonuclease domain in interdomain communication within the HsdR motor subunit of EcoR124I is probed experimentally, confronted with computational predictions and discussed in the light of the fully functional pentameric complex.
Involvement of the endonuclease domain of the EcoR124I restriction-modification complex in interdomain communication